Electrophoretic deposition and constrained sintering of strontium titanate thick films - Amaral, Luis
Thick films of functional oxides are currently substituting counterparts bulk ceramics, as in the case of low loss dielectrics. For SrTiO3 (ST) based compositions it is demonstrated that electrophoretic deposition (EPD), using acetone as a suspension media with iodine addition, is a suitable technology to fabricate 12 mu m thick films. The microstructural analysis of the films sintered at 1500 degrees C shows that highly densified microstructures can be obtained and, by slightly varying the Sr/Ti stoichiometry in the powder composition, increased densification and grain size and enlargement of the distribution with decreasing Sr/Ti ratio can be observed. In spite of the high densification of the films, it is also demonstrated that due to the constraint imposed by the substrate a smaller grain size is observed in thick films as compared to equivalent bulk ceramics. In addition, a preferential vertical pore orientation is observed in ST thick films. These results may have broad implications if one considers that the dielectric losses and dielectric tunability is affected by pore orientation, since it affects the electric field distribution. (C) 2014 Elsevier B.V. All rights reserved.